2004
DOI: 10.1590/s0100-879x2004000900013
|View full text |Cite
|
Sign up to set email alerts
|

Response to an oral calcium load in nephrolithiasis patients with fluctuating parathyroid hormone and ionized calcium levels

Abstract: The response to an oral calcium load test was assessed in 17 hypercalciuric nephrolithiasis patients who presented elevated parathyroid hormone (PTH) irrespective of the ionized calcium (sCa 2+ ) levels. Blood samples were collected at baseline (0 min) and at 60 and 180 min after 1 g calcium load for serum PTH, total calcium, sCa 2+ , and 1.25(OH) 2 D 3 determinations. According to the sCa 2+ level at baseline, patients were classified as normocalcemic (N = 9) or hypercalcemic (N = 8). Six healthy subjects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…A PTH-IR cutoff at 73% has been proposed to differentiate normocalcemic early-stage PHPT patients (PTH-IR <73%) from healthy subjects (PTH-IR >73%) with sensitivity of 95% and specificity of 99.9% [13]. These findings are in agreement with earlier studies on the calcium dependency of PTH secretion [7][8][9][10][11]18]. In fact, PHPT is considered as a biphasic disease, whereby PTH rises first, followed by a rise in serum calcium in later stages of the disease [19].…”
Section: Hyperparathyroidismsupporting
confidence: 86%
See 3 more Smart Citations
“…A PTH-IR cutoff at 73% has been proposed to differentiate normocalcemic early-stage PHPT patients (PTH-IR <73%) from healthy subjects (PTH-IR >73%) with sensitivity of 95% and specificity of 99.9% [13]. These findings are in agreement with earlier studies on the calcium dependency of PTH secretion [7][8][9][10][11]18]. In fact, PHPT is considered as a biphasic disease, whereby PTH rises first, followed by a rise in serum calcium in later stages of the disease [19].…”
Section: Hyperparathyroidismsupporting
confidence: 86%
“…The clinical relevance of the CLT was questioned shortly after publication of the original protocol by Pak et al in 1975 [22]. Since then, more recent studies with refined methodology reliably demonstrated the diagnostic benefits of the CLT, as discussed above [5,[7][8][9][10][11][12][13][14]18,20,21]. However, the therapeutic impact of CLT findings still needs to be evaluated in dedicated studies.…”
Section: Limitations Of the Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Since primary hyperparathyroidism has to be ruled out, serum PTH can be determined either in the same single blood collection or in a further sample in case hypercalcemia has been detected in the former, in order to reduce costs. However, intermittent high levels of serum calcium may represent mild forms of subtle primary hyperparathyroidism (27). A qualitative colorimetric test in spot urine samples to evidence the presence of high amounts of cystine with sodium nitroprussiate can serve as a screening method for cystinuria.…”
Section: Metabolic Evaluationmentioning
confidence: 99%